If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t * 6 + -4 = 14 Reorder the terms for easier multiplication: 6t + -4 = 14 Reorder the terms: -4 + 6t = 14 Solving -4 + 6t = 14 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6t = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 6t = 14 + 4 6t = 14 + 4 Combine like terms: 14 + 4 = 18 6t = 18 Divide each side by '6'. t = 3 Simplifying t = 3
| 40+9=40+8 | | q=p-q/z | | 4x+10=11-10x | | -7f-9(5+6f)= | | -7+8x=-39 | | a*4+2=11 | | 7n+2-4n=5n-10 | | 2pq+6pr+8p+4=3q-3 | | 4y+3=y+3+3y | | a*4+2=12 | | x-7/2=27 | | x^2=x+98 | | 3(x-3)+2x+5+4x= | | 55/2 | | 14=.66666(9y-15) | | (A+1)=25 | | 3-8(-6c+7)= | | 4y-10=-8+4y | | 5/6p=10/9 | | 5x+10+60=-2+14x | | -3-16n=-5 | | 54y^2-42y/(6y) | | 30+3-174=m | | -3-616n=-5 | | x/20+1/2=3/5 | | 3*24+4y=200 | | 4(-3d-8)-2= | | -6x-10=26 | | m/5+8=15 | | 17x(5x-6)=48 | | -17=9x+10 | | .3x-2(1.6x)-8=3(1.9-4.1) |